Significance of nutrition in preventing miscarriage, an ignored but modifiable risk factor - Khan, Mahnoor; Ali, Samra (Journal of the Pakistan Medical Association, 2023)
Madam, Miscarriage or spontaneous abortion is defined as the pregnancy loss occurring before the 24th week of gestation. This term is used when an ultrasound has confirmed an intrauterine pregnancy1. It is the commonest adverse fate of pregnancy, with vaginal bleeding and abdominal pain as alarming symptoms. It is found that around 12-15% of confirmed pregnancies end up in a miscarriage. Although genetic factors (chromosomal abnormalities) top the list, maternal factors, especially nutritional status, can affect the developing embryo and result in early pregnancy foetal demise2. During pregnancy, maternal requirements for energy, macronutrients (carbohydrates, proteins and fats) and micronutrients increase to cope with the physiological changes occurring in the mother’s body and to support adequate foetal development. Two Case control studies have been conducted and have found a preventive effect of milk consumption and dairy products on spontaneous abortion3. There is also an association between decreased animal fat and carotene intake and increased risk of hydatidiform mole, which can ultimately lead to a miscarriage2. Studies proved that not only macronutrients but deficiency of micronutrients also contribute to poor pregnancy outcomes. Some essential micronutrients include iron, magnesium, zinc, vitamin b12 and folic acid., Due to its antioxidant effects, Vitamin C is also required during this stage and contributes to a healthy pregnancy1. Besides deficiencies, even excess of some micronutrients, like caffeine, especially during the pre-pregnancy state contributed to the risk of early pregnancy loss4. Studies have been done to determine the mechanism behind the nutrition’s effect on the outcome of pregnancy. In the pre pregnancy state, nutritional imbalances result in the alteration of germ cell morphology, which hinders the chances of fertilisation of the altered germ cell. In addition to this, nutritional status during the peri-implantation and placental developmental stage (embryonic stage) play a vital role in the establishment of pregnancy and fetal development so any deficiency during this stage increases the risk of miscarriage. Folic acid deficiency during this stage is harmful. Although it mainly results in the development of congenital anomalies in infants, it is seen that by increasing homocysteine levels it can also lead to miscarriage, although the association is still unknown1. Not only undernutrition but overweight and obesity in mothers also lead to poor pregnancy outcomes. ---Continue